Exploring Compatibility Issues Between International Faculty and Their Host Environment: A Case of a Local National University in Japan - Masako Kotake (小竹雅子) (ECNU Review of Education)
Purpose The number of international faculty members in universities is increasing worldwide, and Japan is no exception. However, despite this quantitative expansion, these faculty remain peripheral. Though recent studies have identified various challenges faced by international faculty, they have focused on international faculty's individual experiences and have lacked perspectives from the host institution. To more accurately understand the challenges facing international faculty, this study aims to uncover compatibility issues between these faculty and their host environment. Design/Approach/Methods In this study, I adopted a qualitative case study approach targeting a local national university in Japan. Seven international and six Japanese faculty members were interviewed. Findings The analysis revealed various issues underlying the problems faced by international faculty, including new challenges arising from recent national university reforms. The compatibility issues they experienced can be categorized into the following six areas: organizational goals, systems and practices for hiring and evaluating faculty, division of roles between international and Japanese faculty, organizational support for international faculty, organizational culture and atmosphere, and Japanese society's overall system and values. Originality/Value This study responds to a crucial academic need to understand the host institution's perspective on international faculty recruitment by providing new evidence of the challenges facing international faculty and their host institution in a low-resource environment in the midst of reforms.